DOJO KYOKUSHIN KARATE KALIMANTAN SELATAN - Sandi, Adji Purnama; Sarbini, Gusti Novi (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Kyokushin karate in South Kalimantan is one of the martial arts that still applies a full contact fighting system. The kyokushin karate practitioners in South Kalimantan do not have their own practice sites, and are forced to rent a place to practice. The kyokushin karate dojo in South Kalimantan aims to create a special training ground for practitioners of kyokushin karate who have values from the kyokushin philosophy itself, so that they understand that the art of fighting is only a tool to perfect the body and soul, and can be a strong foundation for human development completely. The philosophy of Kyokushin as a concept will be combined with linguistic methods as the goal of solving problems in the design of this dojo.